Sport for development and Indigenous Australians: a critical research agenda for policy and practice. Issue 2 (4th March 2021) - Lucas, Ryan; Jeanes, Ruth; Diamond, Zane
ABSTRACT: This research note seeks to critically examine Sport for Development (SFD) policies and programming targeting Indigenous Australians. Through a narrative literature review, this article seeks to broaden the discussion surrounding the use of sport as a development tool throughout Australia's Indigenous communities, by considering perspectives within SFD literature that have received limited attention in existing policy and research approaches. The findings of this literature review expose a dominant trend towards positivistic research that reinforces existing approaches, and a lack of criticality surrounding the use of sport as a development tool. This article, therefore, seeks to pose a new research agenda by drawing on international perspectives with the potential to broaden this discussion surrounding the use of sport as a development tool for Indigenous Australians. Issues of conceptual clarity, the use of sport as a mechanism for social control, neoliberalism and neo-colonialism are largely absent from existing literature exploring SFD for Indigenous Australians. Calls to de-colonise SFD are also largely absent from the literature reviewed, and therefore calls for the decolonisation of SFD globally are also considered. Finally, this research note calls for researchers working in this space to engage critically with the use of sport in Indigenous communities, to shift the focus away from the production of 'evidence' to a broader discussion around the use of sport, including how research must contribute to decolonising both policy and practice through privileging Indigenous perspectives and voices.